Combining small-scale screening methods to predict microorganism floatability. (2nd November 2019) - Gulden, S.J.; Riedele, C.; Mueller, S.; Kopf, M.-H.; Nirschl, H.
Graphical abstract: Highlights: Microorganism flotation depends on particle size, bubble size and particle hydrophobicity. Presentation of small-scale screening methods for these flotation key parameters. Their combination allows for prediction and optimization of microorganism flotation. Abstract: Flotation is a common physico-chemical solid-liquid separation technology. It is applied in classical fields like minerals processing, pulp deinking and wastewater treatment and novel fields like biotechnology. The success of flotation is influenced by flotation key parameters. The aim of this study was to present a set of small-scale screening methods for the key flotation parameters particle size, particle hydrophobicity, bubble size and direct particle-bubble interaction. Experiments were performed with the model microorganism S. cerevisiae. Flotation was done in complex fermentation media and in isotonic saline, at varying pH and after flocculant addition. The goal, to combine small-scale laboratory methods to explain, predict and optimize yeast flotation results was achieved. Combining the methods can be used prospectively for wide screening of potential flotation additives, such as collectors, frothers and flocculants and to optimize microorganism floatability.